El sometimiento obligatorio a la Corte Internacional de Justicia en el Pacto de Bogotá - Méndez Chang, Elvira (2023)
Article XXXI of Pact of Bogotá (1948) created the obligation for States parties to submit their disputes to the International Court of Justice “in conformity with” article 36 paragraph 2 of its Statute. In this regard, Honduras held the position that Article XXXI required each State party to make a declaration in accordance with its Statute in order to unilaterally bring the case to the International Court of Justice in the case concerning Border and transborder armed actions (Nicaragua v. Honduras). Then, a question arises: what is the relationship between these two articles? After analyzing international law, jurisprudence and doctrine, the conclusion is that these articles are not related to each other because they are two independent titles of jurisdiction whose differences are found in the source of the State consent, to whom they apply and the disputes that can be settled by the International Court of Justice.